Prospective multicentric validation of a novel prediction model for paroxysmal atrial fibrillation - Schmidt, Constanze; Benda, Sebastian; Kraft, Patricia; Wiedmann, Felix Tobias; Pleger, Sven Torsten; Büscher, Antonius; Thomas, Dierk; Wachter, Rolf; Schmid, Christian; Eils, Roland; Katus, Hugo; Kallenberger, Stefan M. (Clinical research in cardiology, 2021)
The early recognition of paroxysmal atrial fibrillation (pAF) is a major clinical challenge for preventing thromboembolic events. In this prospective and multicentric study we evaluated prediction scores for the presence of pAF, calculated from non-invasive medical history and echocardiographic parameters, in patients with unknown AF status.